PENGARUH KOMPETENSI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA DINAS PERHUBUNGAN PARIWISATA KOMUNIKASI DAN INFORMATIKA KABUPATEN POHUWATO - Umar Sune (AkMen JURNAL ILMIAH, 2016)
The purpose of this study was to determine the effect of competence and discipline on the performance of employees at the Department of Transportation Tourism Communication and Information Pohuwato. This research is a quantitative research. The results showed that the variables of competence and discipline both partially and simultaneously have a significant influence on the performance of employees at the Department of Transportation Tourism Communication and Information Pohuwato. The coefficient of determination (R2) indicates that 56.90% of the variation fluctuation employee performance variable (Y) is able to be explained by the variable competence (X1), and discipline (X2), while the remaining 100 to 56.90% = 43.10 % explained by other variables outside the model.